PRACTICE OF BUYING AND SELLING IN AREAS PROHIBITED IN THE PERSPECTIVE OF ISLAMIC LAW - Yuniartik Yuniartik (JOURNAL OF LAW AND NATION, 2022)
Regional Government of Sambas Regency has arrange problem Street Vendors (PKL). In Sambas Regency Regional Regulation Number 7 of 2006 concerning “Public Order”. Perda this arrange in a manner general related controlling street vendors as well facilitate it with provide land special for trade. Though with various facility place reserved, still many offending merchant rule with sell in places “Prohibited Selling”, one of them namely in the area of Jalan Hasan Saleh, Sambas Regency. This study aims to determine how practice sell buy in a prohibited area selling for Street Vendors (PKL) by the Regional Government of Sambas Regency. Study this use method study field (field research), namely with plunge live to field for get data from parties related like street vendors, good pedestrians ever shop to street vendors, as well officer from the Department of Order as authorized party. Study this use approach juridical and normative that is use rules fiqh and law positive related with the problem under study. Based on results study that sell buy done Street vendors (PKL) on Jalan Hasan Saleh are legitimate in a manner terms and conditions sell buy in Islam. However in in practice, the street vendors selling in locations that do not allowed as the place trade. The consequences of the actions taken can bring harm to sidewalk road users and deny the public good that should be achieved from the regulations that have been formed. This is not in accordance with existing fiqh rules and violates applicable legal regulations. In addition, the practice of street vendors is not based on muamalat principles and principles, namely the principle of prioritizing obligations over rights, the principle of protecting rights, the principle of upholding the values of justice, avoiding elements of persecution and taking advantage of opportunities in adversity. Therefore, the practice of street vendors in the Hasan Saleh street area is classified as a form of work that violates the law, even though the validity of the contract does not cancel the sale and purchase agreement that occurred.